Field notes contributed by Francis L. Moore, fall 1984 - Moore, Francis L.et al (1984)
Field notes were contributed by Francis L. Moore, fall 1984. An albino Red-Tailed Hawk is noted within the report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed